Performance Indices-based Tuning for Barometer-aided Inertial Navigation Systems - Vieira, Leonardo; Silva, Felipe; M. Filho, Rogério; Paiva, Lucas (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2020)
This article aims at investigating tuning methods for the vertical channel mechanization of barometer-aided inertial navigation systems. As main contribution, tuning techniques based on the minimization of performance indices are evaluated, in order to provide mechanization gains with stable errors in altitude and vertical velocity, in addition to quick responses to unit step. The obtained tunings for each of the proposed performance indices are compared with empirical solutions traditionally proposed in the literature. Simulated results demonstrate that the performance-indices-based tunings provide better results regarding the response to unit step and smaller overshoot.